Academic Motivation in Primary and Secondary School Students: The Role of the Perceived Teachers' Motivating Styles - Dušana D. Šakan (University of Belgrade, Teacher Education Faculty, 2023)
The aim of this research was to test whether students' school level (primary school or secondary school level) has a significantly moderating impact on relationships between students' perception of teachers' motivating styles (autonomy, structure and involvement support) and students' academic motivation (intrinsic, extrinsic, introjected motivation and amotivation) in the context of science-mathematics and socio-linguistics subjects. The sample was comprised of 494 students (females = 57.9%) divided into two school levels: 1) students in the final grades of primary school (53.8%); and 2) students in the first two grades of secondary school (46.2%). The results of the moderation analyses indicated that school level did not have a significant moderate influence on the tested relations in the context of socio-linguistic subjects, while it did in the context of science-mathematics subjects. The results of the simple slope tests indicated that the perceived structure support had a positive effect on the realization of intrinsic motivation, especially in the younger respondents, and that both perceived autonomy support and structure support displayed a negative association with amotivation in both age groups of students in the context of the science-mathematics subjects, but that these effects were stronger in the younger respondents. The results offer new insights into how teachers' motivational styles may influence different aspects of students' motivation to learn science-mathematics and socio-linguistics subjects in students at different school levels.